Effectiveness of Bacillus subtilis (Ehrenberg) Cohn. to Suppress the Intensity of Dry Spot Disease (Alternaria solani sor.) on Potato Plant (Solanum tuberosum L.) - Irmawatie, Lilis; Nasrullah, Rizki; Suswana, Suli; Nurdin, Rosyad; Adviany, Ida (Research and Social Study Institute, 2025)
Background: Potato (Solanum tuberosum L.) is one of the priority horticultural crops to be developed in Indonesia. One of the factors affecting the decline in potato productivity is Plant Disturbing Organisms (PDO), namely Alternaria solani Sor. a pathogenic fungus that causes dry spot disease in potato plants. Infection by this disease can reach 100%, resulting in yield losses of up to 78%. One of the biological agents utilized is Bacillus subtilis (Ehrenberg) Cohn. the bacteria for controlling Alternaria solani Sor.Aims: This study aims to determine the effectiveness and optimal concentration of Bacillus subtilis (Ehrenberg) Cohn in suppressing the intensity of Alternaria solani Sor—disease on potato plants.Methods: The research was conducted using the Randomized Block Design (RBD) method, consisting of 6 treatments and 5 replications. The treatment applications used were: Bs-8 (Bacillus subtilis (Ehrenberg) Cohn. 8 ml/liter of water), Bs-10 (Bacillus subtilis (Ehrenberg) Cohn. 10 ml/liter of water), Bs-12 (Bacillus subtilis (Ehrenberg) Cohn. 12 ml/liter of water), Bs-14 (Bacillus subtilis (Ehrenberg) Cohn. 14 ml/liter of water), B1 (Positive control 80% mankozeb concentration 2 grams/liter of water), and B0 (Negative control without Bacillus subtilis (Ehrenberg) Cohn.).Result: The results showed that Bacillus subtilis (Ehrenberg) Cohn. treatment suppressed the intensity of dry spot disease (Alternaria solani Sor.), and the concentration of Bacillus subtilis (Ehrenberg) Cohn. 14 ml/liter effectively suppresses the intensity of Alternaria solani Sor. disease by 88.89% in potato plants.